Prospective Mathematics Teachers’ Creativity in Developing Mathematics Problems Based on Ethnomathematics Context and AKM Framework - Eka Sulistyawati; Dwi Shinta Rahayu (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
Developing instrument tests is an important skill for prospective teachers. The implementation of the Merdeka Curriculum is a means to meet 21st-century skills, one of which is numeracy literacy. This study aims to describe the creativity of prospective teachers and the cognitive level of the developed mathematics problem oriented with Minimum Competency Assessment (AKM) using ethnomathematics context. This qualitative research employed a phenomenological approach, with subjects 7th-semester prospective teachers at an Islamic higher education. Stratified random sampling and maximum variation sampling techniques were used to select 12 students from 96 based on prerequisite course grades. Student creativity in constructing problems was assessed using rubrics based on creativity indicators: fluency, flexibility, and elaboration. The Gwet AC1 Coefficient was used to ensure agreement on the scoring results. Based on the fluency indicator, the results showed that the algebra content was the most difficult to develop, while the measurement and geometry content was the easiest. Based on the flexibility indicator, the majority of the problems were at the application level, and the fewest were at the reasoning level. Considering the level of problems, content on measurement & geometry, data & uncertainty, and algebra were least frequently developed into reasoning-level problems. Based on the problem type in the elaboration indicator, the majority of students developed problems that did not contain new additional information. The least frequently developed problem type was one that included additional information but was not necessary to solve the problem. The findings of this study imply the necessity of measuring teachers' numeracy literacy skills before students' numeracy literacy is developed and measured, as well as the importance of problem development training.